Polymorphisms and Haplotypes in Candidate Genes Related to Angiogenesis and Endothelial Dysfunction in Preeclampsia - Marcelo Rizzatti Luizon; Ana Carolina Taveiros Palei; Valeria Cristina Sandrim (Hindawi Limited, 2012)
Valenzuela and colleagues have recently reviewed some polymorphisms in important candidate genes involved in different pathogenic mechanisms related to preeclampsia (PE) and concluded that various studies in different populations have identified maternal polymorphisms associated with PE. However, we would like to contribute to some studies regarding candidate genes related to angiogenesis and endothelial dysfunction in PE performed in the Brazilian population. Specifically, genotypes and haplotypes formed by polymorphisms of VEGF, eNOS and MMP-9, along with an example of the interaction among these genes in the prediction of PE. Our suggestions may provide additional information with clinical relevance to PE susceptibility.